Banking credit for farm inputs marketing busines - Desai, Bhupat M. (New Delhi, 1996)
This study is on a subject on which the literature is scant. It discusses the rationale for banking credit for farm inputs mar keting business considering both mad and micro perspectives. It then goes on to analyse the past growth in this credit in addition to estimating it for the future for both the nationalized commercial banks and cooperative banks. Two enterprise-level case studies of private farm input dealers who were financed by the State Bank of Saurashtra discusses the methods of loan appraisal and changes required in them, and the working capital management perfor mance of these dealers. Similar issues are discussed in the two case studies on primary agricultural cooperative credit societies (PACS) which were financed by the Banaskantha District Central Cooperative Bank (BDCCB). These case studies reveal that this innovative agricultural credit policy is mutually beneficial to the banks, their clientele and the nation. Two additional case studies on PACS analyse the potential for promoting this credit for such PACS by the BDCCB. The book also discusses how this innova tive agricultural credit may be made a mainstream activity of both the commercial and cooperative banks.
Keywords: Credit